The Impact of Data Control and Delayed Discounting on the Public’s Willingness to Share Different Types of Health Care Data: Empirical Study - Dongle Wei; Pan Gao; Yunkai Zhai (JMIR Medical Informatics)
Abstract BackgroundHealth data typically include patient-generated data and clinical medical data. Different types of data contribute to disease prevention, precision medicine, and the overall improvement of health care. With the introduction of regulations such as the Health Insurance Portability and Accountability Act (HIPAA), individuals play a key role in the sharing and application of personal health data. ObjectiveThis study aims to explore the impact of different types of health data on users’ willingness to share. Additionally, it analyzes the effect of data control and delay discounting rate on this process. MethodsThe results of a web-based survey were analyzed to examine individuals’ perceptions of sharing different types of health data and how data control and delay discounting rates influenced their decisions. We recruited participants for our study through the web-based platform “Wenjuanxing.” After screening, we obtained 257 valid responses. Regression analysis was used to investigate the impact of data control, delayed discounting, and mental accounting on the public’s willingness to share different types of health care data. ResultsOur findings indicate that the type of health data does not significantly affect the perceived benefits of data sharing. Instead, it negatively influences willingness to share by indirectly affecting data acquisition costs and perceived risks. Our results also show that data control reduces the perceived risks associated with sharing, while higher delay discounting rates lead to an overestimation of data acquisition costs and perceived risks. ConclusionsIndividuals’ willingness to share data is primarily influenced by costs. To promote the acquisition and development of personal health data, stakeholders should strengthen individuals’ control over their data or provide direct short-term incentives.